Efektivitas Muraqabah Bagi Aktualisasi Diri Santri - hena khaerulummah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2018)
Muraqabah or introspection is a very important thing for someone, to supervise all their deeds in accordance with God's provisions. The purpose of this study was to determine the effectiveness of muraqabah for the self-actualization of students at the Al-Muawanah Parakansalak Islamic Boarding School in Garut Regency. This study uses qualitative methods, namely a study that produces data in the form of words of the author or oral of observed behavior. While the data sources are teachers or Ustadz and students as subjects and objects in research. Furthermore, the data collection technique uses interviews, observation, documentation. As well as the population of this study amounted to 60 people, but the sample used in this study was 30 Muslim students. And the analysis technique is descriptive method. The results of this study include several aspects of life experienced by the subject when associated with muraqabah, namely aspects of obedience, disobedience, muraqabah in mubah action and self-actualization. Based on the research conducted that muraqabah is able to maintain adab at least 70% of the research subjects totaling 30 people, while 10% sometimes the subject always repents, and the remaining 20% muraqabah does have an effect on students' self-actualization. This is very good when muraqabah is done with effective research to make students who are fully obedient in both spirituality and morality.